Sustainability of the Chinese economic expansion - L. R. Klein; Wendy Mak (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
China's economy has developed in such a startling way that most people - economists or not - place, as starting from about 1978, and many are questioning whether or not it can last? At the same time, they are wondering about its effect on the United States, and the world at large, because China is such a big country. In this presentation, we will look at the question: Can the Chinese economic expansion be sustained? Personally, we believe that it is, in fact sustainable, not necessarily at the present speed, and cannot say confidently that it will, in fact, be sustained. However, we have been bullish on China ever since visiting the country in 1979 and have been tracking the course of forecasts about performance ever since. Now, we are on a bi-weekly schedule of producing and studying the statistical outcome in some detail.
Keywords: 650